Generating a detailed protein profile of Fasciola hepatica during the chronic stage of infection in cattle - Haçarız, Orçun; Baykal, Ahmet Tarık; Akgün, Mete; Kavak, Pınar; Sağıroğlu, Mahmut Şamil; Sayers, Gearoid Patrick (Wiley-Blackwell, 2014)
Fasciola hepatica is a trematode helminth causing a damaging disease, fasciolosis, in ruminants and humans. Comprehensive proteomic studies broaden our knowledge of the parasite's protein profile, and provide new insights into the development of more effective strategies to deal with fasciolosis. The objective of this study was to generate a comprehensive profile of F. hepatica proteins expressed during the chronic stage of infection in cattle by building on previous efforts in this area. The approach included an improved sample preparation procedure for surface and internal layers of the parasite, the application of nano-UPLC-ESI-qTOF-MS (nano-ultra-performance LC and ESI quadrupole TOF MS) integrated with different acquisition methods and in silico database search against various protein databases and a transcript database including a new assembly of publically available EST. Of a total of 776 identified proteins, 206 and 332 were specific to the surface and internal layers of the parasite, respectively. Furthermore, 238 proteins were common to both layers, with comparative differences of 172 proteins detected. Specific proteins not previously identified in F. hepatica, but shown to be immunomodulatory or potential drug targets for other parasites, are discussed.
WOS: 000337616100009
PubMed ID: 24733753
Keywords: Fasciola Hepatica; Fraction; Microbiology; Tegument; Trematode